Surrogacy as an Alternative for Depressive Infertile Couples - Shyamantak Misra; Prafulla Chandra Mishra (Indian Journal of Forensic Medicine & Toxicology, 2021)
This piece of work aims to provide a clear picture of the available alternatives to the intending infertilecouples and how far surrogacy is acceptable as an alternative to the prolonged infertility treatments thatultimately lead to depression symptoms like anxiety and other expressed emotional patterns. It’s a bestowedpower on women to cherish the experience of motherhood but unfortunately not all the women are luckyenough to conceive and enjoy the joyous feeling of being a mother and experiencing motherhood. It’susually a dubious decision to make for the intending infertile couples whether to continues with the infertilitytreatments to have a child of their own or opt for an alternative like Surrogacy or Adoption. This article statesthe need of taking up an alternative before it’s too late and emphasizes on the reasons for taking up surrogacyas an alternative above the other available ones and also mentions the reasons why couples do not opt forsurrogacy so that one takes care of the same while choosing the same. The procedure to be followed by suchcouples while selecting this alternative has also been stated so that they find themselves in a better positionthan the once suffering to get through.